SHELL MICROSTRUCTURE AND MINERALOGY OF THE MOLLUSC SPECIES ANADARA UROPIGIMELANA (BORY DE SAINT-VINCENT, 1827), TIVELA STEFANINII (NARDINI, 1933) AND OLIVA BULBOSA (RÖDING, 1798) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2025)
Mollusc shells are composite structures made of calcite and/or aragonite crystals and biopolymers, arranged in a great variety of microstructures. The formation of shell microstructures is affected by environmental and physiological factors and differences among microstructural types are believed to be of phylogenetic and adaptive biomechanical significance. Here, we characterise and illustrate for the first time, through SEM and XRD analyses, the shell microstructure and mineralogy of specimens of the bivalves Anadara uropigimelana (Bory de Saint-Vincent, 1827) and Tivela stefaninii (Nardini, 1933), and of the gastropod Oliva bulbosa (Röding, 1798), collected in the Upper Holocene HAS1 settlement and in a shell midden in the Khor Rori Archaeological Park (Oman). Anadara uropigimelana shows an aragonitic shell with an outer crossed lamellar layer, an inner complex crossed lamellar layer and an irregular simple prismatic pallial myostracum; periodic bands of dendritic nondenticular composite prisms occur in the outer part of the outer layer, reflecting seasonal changes in water temperatures and growth rates. Shells of Tivela stefaninii are aragonitic with an outer composite prismatic layer, a middle crossed lamellar layer and an inner complex crossed lamellar layer, whereas those of Oliva bulbosa are characterised by an irregular alternation of aragonitic crossed lamellar layers; a transitional layer defined by the occurrence of tidally controlled growth lines, a crossed lamellar callus and a myostracal layer are also described are also described in Oliva bulbosa. With this investigation, we provide novel microstructural and mineralogical data on these poorly known mollusc species, providing useful characters for phylogenetic, evolutionary, crystallographic, and palaeoenvironmental studies.
Keywords: Bivalve; gastropod; biomineral; Scanning Electron Microscopy; X-Ray Diffraction.